The Image of Chinese Law in the Writings of European Missionaries of the 16th Century - Yan, He (Sinología hispánica. China Studies Review, 2024)
In the mid-1600s, European missionaries journeyed to China, producing a wealth of travel diaries, scholarly writings, and reports. These missionaries meticulously documented China's political and legal systems. This study delves into the Ming Dynasty missionaries’ interpretations of Chinese law, highlighting the historical context and its mutual influence with European culture. Our findings indicate that, during a certain period, Chinese law was portrayed in European culture as the cultural “other”. This representation not only served as a self-examination and reflection for European culture but also mirrored its understanding of its own cultural identity. While grounded in reality, these descriptions largely represent European cultural projections.